Graph Database: An Alternative for Relational Database - Vyawahare, H.R; Karde, P.P; Thakare, V.M (International Journal of Computer Sciences and Engineering, 2019)
Relational Database Management System (RDBMS) has been the power house of database industry since decades. However with the evolution of big data, they are loosing their importance due to many reasons. With the rapid growth in internet and social network, graph databases are seen as an promising alternative to relational database for determining relationships optimally and quickly. These databases can be of great help to the companies struggling with traditional databases and want some new database that can replace these legacy databases. This paper presents a theoretical investigation and comparison of the relative usefulness between relational database (MySQL) and the graph database (Neo4j).